PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN DAN PENGAMBILAN KEPUTUSAN PEMBELIAN RUJAK BUAH ULEK DI ISTANA RUJAK BENGKULU - Desi Aryani; Nyayu Neti Arianti; Basuki Sigit Priyono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This study aims to analyze consumers’ perceptions of the marketing mix and purchasing decision of ground fruit salad (rujak buah ulek) at the Istana Rujak.  Respondents in this study are 96 people, namely those who had bought and consumed rujak buah ulek of the Istana Rujak at least twice. Respondents were taken accidentally. Consumers’ perceptions and purchasing decision process were analyzed descriptive qualitatively.   The results showed that consumers’ perceptions on all marketing mix components, namely product, price, promotion, and place at Istana Rujak, were in good category. Most rujak buah ulek Istana Buah consumers stated that they needed to carry out all stages of the purchasing decision process, namely recognition need, information search, evaluation of alternatives, purchase decision, and post-purchase evaluation.Key words: marketing mix, purchasing decision, rujak buah ulek